CHANGES IN THE OXIDATIVE AND ANTIOXIDANT SYSTEMS OF THE KIDNEYS IN METABOLIC SYNDROME (Global Conference on Medical and Health Sciences, 2026)
Metabolic syndrome (MetS) is one of the major challenges in modern medicine. Abdominal obesity, hyperglycemia, dyslipidemia, and arterial hypertension are key factors contributing to the development of kidney injury [1].Experimental studies have demonstrated significant structural and functional alterations in renal cell membranes during the development of glomerular injury associated with enhanced lipid peroxidation (LPO) [2]. An experimental study by T.L. Pallone [3] showed that oxidative stress may be induced independently or simultaneously in both the renal cortex and medulla. Moreover, the superoxide anion initiates oxidative stress throughout all regions of the kidney, whereas hydrogen peroxide predominantly affects the renal medulla.
Keywords: Abdominal obesity, hyperglycemia, dyslipidemia, and arterial hypertension